Remoção de BTEX em solução aquosa por adsorção usando zeólita sintética modificada - Vidal, Carla Bastos (2011)
BTEX (benzene, toluene, ethylbenzene and xylenes) are organic compounds of particular concern due to their toxicity. BTEX occur in the environment as products of incomplete oxidation of fossil fuels, thus polluting the atmosphere. Also, the disposal of industrial effluents, oil spills, and fuels leaks at gas stations are sources of BTEX contamination in soil and water, resulting in their accumulation mainly in groundwater. Conventional and advanced technologies have been used for treatment and remediation of contaminated areas. Zeolites include many natural and synthetic minerals that have characteristics in common. The potential application of synthetic zeolites in the environmental field has been reported worldwide. In this work, surface modification of synthetic zeolite Y by Hexadecyltrimethylammonium (HDTMA-Br) was studied, as well as its application for removal of BTEX from aqueous solution. The zeolite cation exchange capacity (CEC) was evaluated and three modifications of the zeolite with surfactant HDTMA-Br were carried out, with results corresponding to 50%, 100%, and 200% of CEC. The results of BTEX adsorption experiments onto both synthetic and modified zeolites showed that the ZMS-100 was the most efficient modified zeolite for BTEX removal. Adsorption isotherms and kinetics study of this material were carried out. Kinetics study indicated that multicomponent adsorption equilibrium was reached in 6 hours and followed pseudo-second order kinetics. Langmuir, Freundlich, Redlich-Peterson and Temkin models were used to evaluate the adsorption capacity of BTEX by ZMS-100. Temkin model was found to be suitable all BTEX in a multicomponent system, and maximum adsorption capacities of 175, 32, 164.58, 162.22, 152.41, and 150.42 mg g-1 were observed for m-xylene, p-xylene, o-xylene, ethylbenzene, toluene and benzene, respectively. Regeneration cycles of the zeolite were also performed and the results showed that the adsorbent can be used only for one adsorption cycle for the removal of benzene, while for the other BTEX up to four regeneration cycles can be achieved.